2015
DOI: 10.5858/arpa.2015-0116-ra
|View full text |Cite
|
Sign up to set email alerts
|

Review of Telemicrobiology

Abstract: Context Microbiology laboratories are continually pursuing means to improve quality, rapidity, and efficiency of specimen analysis in the face of limited resources. One means by which to achieve these improvements is through the remote analysis of digital images. Telemicrobiology enables the remote interpretation of images of microbiology specimens. To date, the practice of clinical telemicrobiology has not been thoroughly reviewed. Objective Identify the various methods that can be employed for telemicrobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…For routine surgical pathology, it is the authors' experience that scanning glass slides using a low-magnification objective (eg, 320) appears to be sufficient. 17 Scanning at higher magnification (eg, 340 or greater) generates images of greater resolution, which may be necessary for identifying small objects such as microorganisms, 18 although routine scanning at 340 may be preferred by some pathologists. There are instruments that can perform oil-immersion scanning (eg, Aperio CS-O and VERSA scanners [Leica Biosystems]), which is very helpful when dealing with hematopathology smears.…”
Section: Scanning Devicesmentioning
confidence: 99%
“…For routine surgical pathology, it is the authors' experience that scanning glass slides using a low-magnification objective (eg, 320) appears to be sufficient. 17 Scanning at higher magnification (eg, 340 or greater) generates images of greater resolution, which may be necessary for identifying small objects such as microorganisms, 18 although routine scanning at 340 may be preferred by some pathologists. There are instruments that can perform oil-immersion scanning (eg, Aperio CS-O and VERSA scanners [Leica Biosystems]), which is very helpful when dealing with hematopathology smears.…”
Section: Scanning Devicesmentioning
confidence: 99%
“…In addition, the CDC's Division of Parasitic Diseases and Malaria offers a telediagnostic service (http://www.cdc.gov/dpdx/ contact.html) that can provide a rapid diagnosis, usually to the species level (11). A cost-savings analysis has showed that the CDC's telediagnostic service is one-twentieth the cost of normal specimen submissions to the CDC and can provide results within 1 to 2 h during normal business hours of operation (18,19). In a study evaluating data between October 2005 and September 2010, the CDC's telediagnostic service was able to confidently obtain a species-level identification in 70% of the cases (n ϭ 1192) (18).…”
Section: Diagnosismentioning
confidence: 99%
“…Telepathology is a growing component of the practice of pathology and laboratory medicine, which includes telemicrobiology. [ 1 2 3 ] Telemicrobiology is an important and growing component of clinical microbiology informatics. [ 3 4 ] Telemicrobiology has been incorporated into routine use by some microbiology core laboratories that supports satellite laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 ] Telemicrobiology is an important and growing component of clinical microbiology informatics. [ 3 4 ] Telemicrobiology has been incorporated into routine use by some microbiology core laboratories that supports satellite laboratories. Telemicrobiology has also been used for seeking expert consultation, such as the consultation services established by the Centers for Disease Control and Prevention's (CDC) Division of Parasitic Diseases and Malaria's service for diagnostic assistance (DPDx).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation